Using the distributive property of multiplication over addition, 2*[2 - 2] = 2*[2 + (-2)] = 2*2 + 2*(-2)LHS = 2*0 = 0
RHS = 4 + 2*(-2)
Therefore 2*(-2) = -4 and, by commutativity, -2*2 = -4
Next
-2*[2 - 2] = -2*[2 + (-2)] = -2*2 + -2*(-2)
LHS = -2*0 = 0
RHS = -4 + -2*(-2)
Therefore -2 times -2 = +4
Chat with our AI personalities
2(x + 2)(x - 2)(x2 + 2x + 4)(x2 - 2x + 4)
2 x 2 = 4 8 x 0.5 = 4
k = 7 x^4 - 5x^3 + 7x^2 + 3x - 10 = (x + 1)(x - 2)(x^2 - 4x + 5)
(x - 4)(x + 9)
To solve the equation "x times y minus z equals 13," we need to set up the equation as follows: xy - z = 13. Since we are looking for three unknowns, there are multiple solutions to this equation. One possible solution could be x = 5, y = 3, and z = 2, as 5 times 3 minus 2 equals 13.